1991
DOI: 10.4049/jimmunol.146.11.3747
|View full text |Cite
|
Sign up to set email alerts
|

Selective stimulation of human T cells with streptococcal erythrogenic toxins A and B.

Abstract: Streptococcal exotoxins have been implicated in the pathogenesis of a toxic shock-like syndrome and scarlet fever. Previous studies have demonstrated that these toxins are potent stimulators of human T cells and have structural homology to staphylococcal enterotoxins. In the current study, we investigated the mechanism by which streptococcal erythrogenic toxins type A (SPEA) and B (SPEB) activate T cells and compared it with anti-CD3 and the known "superantigen" staphylococcal enterotoxin B. SPEA was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An earlier study reported that TRBV12-3/12-4 + cells became activated in response to stimulation with SpeC 62 . However, this result was later questioned by the same group of investigators 63 , who suspected contamination of the original SAg preparation with SpeA, which is known to exhibit specificity for TRBV12-3/12-4 + TCRs 64 , 65 . In particular, they found that recombinant SpeC did not induce the secretion of IL-2 from Jurkat cells expressing TRBV12-3/12-4 + TCRs 63 , even in the presence of Raji cells to compensate for a lack of HLA-DQ and HLA-DR 66 .…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study reported that TRBV12-3/12-4 + cells became activated in response to stimulation with SpeC 62 . However, this result was later questioned by the same group of investigators 63 , who suspected contamination of the original SAg preparation with SpeA, which is known to exhibit specificity for TRBV12-3/12-4 + TCRs 64 , 65 . In particular, they found that recombinant SpeC did not induce the secretion of IL-2 from Jurkat cells expressing TRBV12-3/12-4 + TCRs 63 , even in the presence of Raji cells to compensate for a lack of HLA-DQ and HLA-DR 66 .…”
Section: Discussionmentioning
confidence: 99%